Analisis Potensi Obyek Wisata dan Kesiapan Masyarakat dalam Pengembangan Desa Wisata Berbasis Masyarakat di Kawasan Danau Linting Kabupaten Deli Serdang - Sekar Indah Putri Barus; Pindi Patana; Yunus Afifuddin (Peronema Forestry Science Journal, 2013)
The research about the value of potential and  attraction of tourism object in Linting Lake area hasn’t been never conducted. The research has aims to analyzed the potential and attraction of nature tourism in Linting Lake area and community appraisal in developing the tourism village in Linting Lake area. Questioneries involved the visitors, the public, staff of the Forest Ministry, and staff of Tourism Ministry. The results of the research showed that the potential of natural resources in Sibunga –bunga village are hot water sources, caves, and lime stones. Evaluation of object and tourism attraction is categorized to be feasible for further development. People are willing to participate in developing their village to be one of the tourism village. Keywords: ecotourism, tourist attraction, Tourism Village, Lake Linting